Improving Physical Health Assessments in Alcohol Use Disorder: A Service Audit - Mario Lepore; Chris Joseph; Mike Kelleher (BJPsych Open)
Aims: Individuals seeking support from drug and alcohol services often experience significant physical health challenges, with many presenting with comorbid conditions such as liver disease. Early identification of these conditions is vital for ensuring holistic and effective patient care. This audit aimed to evaluate the proportion of clients with alcohol use disorders who had recently undergone blood tests, Fibrosis-4 (FIB-4) scoring (a non-invasive marker for liver fibrosis) and FibroScan. The audit also sought to identify gaps in current clinical practices and provide recommendations to optimise care pathways for this population.